Numerical analysis of natural rubber bearing equipped with steel and shape memory alloys dampers. (August 2021) - Sheikhi, Javad; Fathi, Mojtaba; Rahnavard, Rohola; Napolitano, Rebecca
Abstract: In this paper, the behavior of a natural rubber bearing system (NRBs) equipped with U-shaped dampers is investigated. The U-shaped dampers consist of shaped memory alloy (SMA), structural steel (SS), and combination of both SMA and SS. The combined Mooney-Rivlin and Prony models in ANSYS software is selected for modeling the rubber material. Two cyclic static and dynamic time-history analyses were selected to evaluate the behavior of NRBs equipped with dampers. The results show that the SMA dampers made of FeNiCuAlTaB with 13.5% super-elastic strain and low austenite finish temperature are the most appropriate candidates for use in high shear strain, steel-rubber bearings. The results showed that finite element analyses are able to accurately simulate the mechanical behavior of the damper. Having confirmed the validity of the analysis, the optimum thickness ratio of SMA to SS (tSMA /tSS ) to maximize dissipated energy and minimize residual deformation for the dampers was found to be one. The results show that each damper typology has unique benefits; while the U-shaped SMA damper has super-elastic behavior and residual deformation reversibility, the SS dampers significantly increase the energy dissipation capacity. Lastly to illustrate how this could be instrumented on real-world infrastructure, several bridge models, with steel decks and concrete piers isolated by NRBs equipped with steel and SMA dampers, were evaluated.